Addition of Vitamin C on Diet to Improve Immunity on Tiger Grouper, Epinephelus fuscoguttatus to Infection Viral Nervous Necrosis - F. Johnny; K. Mahardika; I.N.A. Giri; D. Roza (Jurnal Akuakultur Indonesia)
An attempt with a purpose to improve the fish seed immunity tiger grouper, Epinephelus fuscoguttatus to infection viral nervous necrosis (VNN) with addition of vitamin C have been done in Gondol Research Institute for Mariculture, Bali.  Fish seed tiger grouper counted 400 fishes with wight between 35-55 disperse gram into 4 polycarbonate tanks volume of 1000 litres with density of 100 fish/tank.  Each tank is equipped with flow-through water system and aeration.  Experimental diets were formulated to have the same nutrients content except of vitamin C stable form (L-ascorbyl-2-Phosphate-Magnesium) with different dose, that is 0; 300; 600; 1.200 mg/kg diet was added to each formula.  Experimental diets were prepared as dry pellet using freeze dryer Fish fed experimental diets twice everyday during 60 day. After 20, 40, and 60 days after treatment test to challange with VNN. Perception of test fish immunities parameter done to phagocytic activity (PA), make of phagocytic index (PI) and lysozyme activity (LA). Attempt result indicated that addition of vitamin C in diet dose between 600-1,200 mg/kg after 60 treatment day yield highest survival rate, PA and LA compared to other treatments.